Eksistensi Wali Nikah: Analisis Terhadap Undang-Undang Hukum Keluarga Islam Indonesia dan Lebanon - Nurfitriani; Atun Wardatun; Teti Indrawati Purnamasari (Maqasid: Jurnal Studi Hukum Islam, 2025)
This study discusses the existence of marriage guardians from the perspective of Islamic family law by comparing the regulations in force in Indonesia and Lebanon. These two countries, although both adhere to Islamic law as the basis for regulating marriage, have fundamental differences in placing the role and position of marriage guardians. In Indonesia, the existence of a guardian is an absolute requirement in the implementation of a marriage contract as regulated in the Compilation of Islamic Law (KHI), while in Lebanon, which has a plural legal system and is segmented based on sects, there are variations in the application of guardian requirements depending on the school of thought adopted. This study uses a normative legal approach with a comparative analysis method to examine the similarities and differences in the concept of marriage guardians in the two countries. The results of the study show that these differences are influenced by the social, political background, and diversity of schools of thought recognized in their respective legal systems. This study is expected to contribute to the development of discourse on the harmonization of Islamic family law in a pluralistic global context.